Quality requirements for cross-border care in Europe: a qualitative study of patients', professionals' and healthcare financiers' views. (2nd February 2009) - Groene, O; Poletti, P; Vallejo, P; Cucic, C; Klazinga, N; Suñol, R
Abstract : Background: In the past decade the issue of patient mobility has emerged on the European health policy agenda. Although the volume of patients crossing borders to obtain healthcare is low, it is increasing continuously and, due to its legal, financial and medical implications, has generated considerable interest among health policy and other decision makers. However, there is little information available on the safety and patient-centredness of cross-border care and neither governments nor citizens have an explicit basis for comparing healthcare delivery in Europe. Methods: This study investigated the viewpoints of patients, professionals and healthcare financiers on the safety and patient-centredness of cross-border care. Qualitative interviews were carried out during 2005 and early 2006 with 40 patients, 30 professionals (doctors, nurses and managers) and 3 healthcare-financing bodies. Results: Although cross-border care has become a common issue in many European countries, there remain uncertainties on the side of each of the parties addressed—patients, professionals and financiers—with regard to the provision of cross-border care. One of the most striking results of this project is the current lack of research on systematic knowledge on the quality of cross-border care. Conclusion: Many of the issues identified through this research may have a potential impact on the quality and safety of cross-border care and will support further investigation and help shape the health policy agenda on patients crossing borders in European Union countries.